From policy to practice: Addressing bycatch for marine species-at-risk in Canada. (December 2022) - Jubinville, Isabelle; Shackell, Nancy L.; Worm, Boris
Abstract: Unintended bycatch of depleted or vulnerable marine species is an unsolved conservation issue that undermines the sustainability of fisheries worldwide. In Canada, policy incentives to address bycatch of vulnerable species-at-risk have become more prominent in recent years. Yet bycatch risk has been difficult to quantify and mitigate, in part due to large data gaps in fisheries observation and monitoring. Here we suggest the use of novel modelling frameworks to optimize spatial management strategies for bycatch mitigation. We utilize spatiotemporal modeling of fisheries-independent survey data to predict high-risk regions for three at-risk skates (family Rajidae) in Atlantic Canada. We use these identified regions to evaluate the relative reduction in bycatch risk that can be expected by closing targeted bycatch-protection zones on the western Scotian Shelf to bottom-trawl fishing, and further examine the relative costs to the fishing industry that such closures may impose. We show that when closures are precisely targeted on high-bycatch risk areas, relative costs to industry are minimal by affected fishing area (1.25 ± 0.62 % total area) or displaced landings (0.28 ± 0.14 % by weight of catch). To reduce bycatch risk by 50 % for all three vulnerable skates, less than 10 % of landed catch weight is displaced. These results can be used to reduce bycatch encounters for any endangered, threatened or protected species through spatially targeted conservation measures. We conclude that new approaches to the analysis and mitigation of spatial-temporal bycatch patterns can help to meet regulatory or market-driven requirements for bycatch reduction at low cost.